CRISPR-Cas9 in gene therapy: much control on breaking, little control on repairing - Daneshvar, Kaveh (PeerJ PrePrints, 2015)
Recent advances in CRISPR-Cas9 genome editing tool have made great promises to basic and biomedical research as well as gene therapy. Efforts to make the CRISPR-Cas9 system applicable in gene therapy are largely focused on two aspects: 1) increasing the specificity of this system by eliminating off-target effects, and 2) optimizing in vivo delivery of the CRISPR-Cas9 DNA constructs to target cells and limiting the expression of Cas9 and gRNA to prevent immune responses. Moreover, there is an unnoted but crucial consideration about the mode of DNA repair at the lesion caused by CRISPR-Cas9. In this commentary, I briefly highlight recent publications on in vivo use of the CRISPR-Cas9 system in gene therapy. I then discuss concerns about the off-target activity and immune responses triggered by the use CRISPR-Cas9 in gene therapy. Following this, I focus on the undesired on-target DNA repair events that can occur as a result of the activity of CRISPR-Cas9. This concise commentary sets itself apart from previous perspectives by focusing on the modes of DNA repair employed following a CRISPR-Cas9 induced genomic insult, and by carefully weighing the benefits of the outcomes. In particular, the present manuscript underscores the need for more study on controlled DNA repair in systems targeted with CRISPR-Cas9 genome editing tools.
Keywords: CRISPR-Cas9; Genome Editing; Gene therapy; DNA repair; Double strand break; homologous recombination; non homologous end joining